Guidelines for Parental Involvement in Transitional Bilingual Education - Massachusetts State Dept. of Education, Boston. Bureau of Transitional Bilingual Education; Massachusetts State Dept. of Education, Boston. Bureau of Transitional Bilingual Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The guidelines outlined in this pamphlet were developed in cooperation with members of local parent advisory councils and school officials. The guidelines describe the rationale for parental involvement, the specific steps to be taken in organizing parent advisory councils, and the roles and responsibilities of these councils. (CLK)
ERIC Note: For related documents, see FL 009 328-329.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Bilingual Education; Bilingual Students; Elementary Secondary Education; English (Second Language); Guidelines; Non English Speaking; Parent Associations; Parent Participation; Parents; Program Development; Transitional Bilingual Education; Massachusetts; Guides, General